Ta’lim Maharah al-Qira’ah Ittishaliyan bi Istikhdam al-Nushush al-‘Arabiyyah al-Ashliyyah wa Ta’tsiruha fi Tanmiyyah wa Tahifz al-Qira’ah Laday al-Thalabah - Dewi, Intan Sari; Adam Ibrahim, Faisal Mahmoud; Syuhadak, Syuhadak (Institut Agama Islam Negeri Curup, 2022)
This research attempts to explore the use of Arabic authentic texts in teaching reading skills communicatively in the classroom and its impact on developing reading skills and motivating students to learn to read. To address this issue, quantitative research was conducted on 34 students from the Department of Arabic Language and Literature at the State Islamic University of Tulungagung. The participants were divided into two groups: an experimental group and a control group using four authentic Arabic texts that were taken from online newspapers with appropriate readability. It was made to measure before and after reading using the original Arabic texts. Independent samples of the t-test and the group acquisition method in the pre- and post-test revealed that the use of authentic reading texts has a positive effect on the reading comprehension of second-stage students. From the pre-test to the post-test, there was a significant difference (0.001 < 0.05) before and after the implementation of the authentic reading texts. Also, the authentic texts affected students' motivation to read. Through observation and interview, it is obtained that the proper use that is built in the light of the authentic Arabic texts has a positive effect on the students’ motivation to read, in that the students have the desire to read the texts more than they were, because they are interested in texts that describe the life and real culture from the learned language.